1994
DOI: 10.1177/070674379403900510
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hypotension Associated with Combined Lithium and Chlorpromazine Therapy: a Case Report and a Review

Abstract: The case of a patient who developed a severe hypotensive reaction with a persistent hemianaesthesia following the addition of lithium carbonate to her treatment regimen is described. The patient had been receiving chlorpromazine therapy for the management of hypomania and the addition of lithium carbonate to the chlorpromazine produced a severe hypotensive episode which compromised her neurological functioning. Only three doses of lithium carbonate had actually been taken by the patient. This type of hypotensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
1998
1998

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In another study (35), two of 30 patients receiving lithium and a neuroleptic developed severe tremor. Cases in which use of lithium combined with a neuroleptic resulted in severe neurotoxicity, such as delirium, seizures, tardive dyskinesia, encephalopathy, or EEG abnormalities, have been reported, as have hypotension and cardiac arrhythmias (44)(45)(46)(47)(48)(49)(50)(51)(52). However, Krishna et al (34) reported that neurologic symptoms are usually mild and resolve with discontinuation of medication.…”
Section: Combinations With Lithiummentioning
confidence: 99%
“…In another study (35), two of 30 patients receiving lithium and a neuroleptic developed severe tremor. Cases in which use of lithium combined with a neuroleptic resulted in severe neurotoxicity, such as delirium, seizures, tardive dyskinesia, encephalopathy, or EEG abnormalities, have been reported, as have hypotension and cardiac arrhythmias (44)(45)(46)(47)(48)(49)(50)(51)(52). However, Krishna et al (34) reported that neurologic symptoms are usually mild and resolve with discontinuation of medication.…”
Section: Combinations With Lithiummentioning
confidence: 99%